Cross-sectional study of the differences between measured, perceived and desired body size and their relations with self-perceived health in young adults: The Tromsø Study - Fit Futures 2 - Sand, Anne-Sofie; Furberg, Anne-Sofie; Lian, Olaug S; Nielsen, Christopher Sivert; Pettersen, Gunn; Winther, Anne; Emaus, Nina (Scandinavian Journal of Public Health, 2017)
Source at http://dx.doi.org/10.1177/1403494817690941 Aims: The aim of this study was to explore the relationships between measured body size (body mass index (BMI)), perceived body size, weight change wishes and self-perceived health in young adults. Methods: The participants were recruited from a school-based population study in Norway, the Tromsø Study: Fit Futures 2, carried out in 2012–2013. A total of 629 young women and men (aged 18–23 years) reported on the main variables. The data were collected through weight and height measurements and questionnaires. The analyses were performed with descriptive statistics, the χ2 test and Student’s t-test. Results: A total of 20% of the women and 28% of the men were overweight or obese. There were considerable discrepancies between the measured BMI and perceived body size in both sexes. A substantial number of participants wanted to change their weight. Among the 174 women who reported that they were trying to lose weight, as many as 57 (32.8%) had a low normal weight (BMI 18.5–21.9 kg/m2). Correspondingly, among the 66 men who reported that they wanted to gain weight, as many as 19 (28.8%) had a high normal weight (BMI 22–24.9 kg/m2). We found no relation between body size perceptions, weight change wishes and self-perceived health. Conclusions: Discrepancies between measured and perceived body size and weight change wishes are common findings in young adults. The lack of relation with self-perceived health found in our study is surprising and not easy to interpret. To gain more knowledge about these matters, further research, including both qualitative and quantitative studies, is needed.